Arab Revolutions and Beyond The Middle East and Reverberations in the Americas - Alnasseri, Sabah; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
This edited volume brings together global perspectives on twenty-first century Arab revolutions to theoretically and methodologically link these contemporary uprisings to resistance and protest movements worldwide, above all in the Americas. In their analyses of these transformations, the international contributors engage in an exploration of a variety of themes such as social movements and cultures of resistance, geopolitical economics, civic virtue, identity building, human rights, and foreign economic and political influence. What is the historical significance of these revolutions? What are the implications beyond the Middle East? And how are struggles in other regions of the world being influenced by these events? These heretofore largely unanswered questions are addressed in this collection, developed from presentations at a 2013 international conference on the "Arab Revolutions and Beyond" at York University, Toronto, Canada.
Introduction; Sabah Alnasseri -- 1. The Geopolitical Economy of the Arab Revolutions; Radhika Desai -- 2. "Dignity" as Global Civic Virtue: Redefining Democracy in the Era of Neoliberal Governmentality; F. Tsibiridou and M. Bartsidis -- 3. The Arab Revolutions of 2011 and Iran 2009: Identities and Differences; Kevon B. Anderson -- 4. Human Rights from Below and International Poverty Law: Comparative Aspects of the Arab Spring and the Egyptian Revolution of 2011, and Their Lessons for Latin America and Mexico; Camilo Pérez-Bustillo -- 5. Public Space without Demands: Understanding Travelling Theory and Practice in Occupy and Transnational Protests; Martha Balaguera -- 6. Class, State, and the Egyptian Revolution; Sabah Alnasseri -- 7. A War of Position in Palestine; Phillip Leech -- 8. Resistant Rationalities? Some Reflections on Shi'i Movements in Lebanon; Sarah Marusek -- 9. Coda; Sabah Alnasseri.
Keywords: International relations; Peace; Economic policy; Middle East-Politics and governm; Political science